2016
DOI: 10.1016/j.cct.2016.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Can atorvastatin with metformin change the natural history of prostate cancer as characterized by molecular, metabolomic, imaging and pathological variables? A randomized controlled trial protocol

Abstract: Can atorvastatin with metformin change the natural history of prostate cancer as characterized by molecular, metabolomic, imaging and pathological variables? A randomized controlled trial protocol This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“… 28 , 30 Thus, patients with lower grade tumors may be amenable to SP-mediated in vitro or magnetic resonance spectroscopic imaging (MRSI)-mediated in vivo assessment or monitoring as a potential substitute for repeat biopsy in active surveillance. 28 , 31 …”
Section: Discussionmentioning
confidence: 99%
“… 28 , 30 Thus, patients with lower grade tumors may be amenable to SP-mediated in vitro or magnetic resonance spectroscopic imaging (MRSI)-mediated in vivo assessment or monitoring as a potential substitute for repeat biopsy in active surveillance. 28 , 31 …”
Section: Discussionmentioning
confidence: 99%
“…The chemo-preventive effect of statin in prostate cancer remains to be investigated [198,199]. An RCT was designed to assess the potential synergies of metformin and atorvastatin for prostate cancer but has been terminated due to the low incidence of eligible patients [200].…”
Section: Prostate Cancermentioning
confidence: 99%
“…[11][12][13] More importantly, during the termination step various small molecules are produced, which induce oncogenic mutations and activate oncogenic pathways, promoting carcinogenesis. 14,15 Some studies have reported that a high-fat diet can result in increased estrogen concentrations in the serum, potentially through increased de novo synthesis. 16 Some other studies elucidated that the histopathological markers -estrogen receptor (ER), progesterone receptor (PR) and human epidermal growth factor receptor 2 (HER2/neu) expression) are frequently associated with breast cancer.…”
Section: 8mentioning
confidence: 99%